PEMENUHAN HAK MENYAMPAIKAN KELUHAN BAGI ANAK DI LEMBAGA PEMASYARAKATAN ANAK BLITAR - Prabowo, Bagus Bayu (Jurnal Mahasiswa Fakultas Hukum, 2015)
Abstract This scientific article discuss the fulfillment of the rights lodge complaints for Children in a correctional institution the son of Blitar, associated with the principle of child protection that was found in the Act of number 11/2012 about Criminal Justice Systems Child.The problems raised by the writer, on the implementation of fulfilling the right lodge complaints for children in a correctional institution the son of Blitar that reflects the principle of child protection. Was continued by knowing obstacles and the efforts made by a correctional institution in the son of blitar fulfilling the right lodge complaints for children in a correctional institution the son of Blitar. Empirical research is kind of the prevailing approach to yuridicial sociological. Of the results of research we can see that the implementation of the right lodge complaints to the correctional institution in the blitar have been reflecting the principle of child protection contained in the Act of number 11/2012 about Criminal Justice Systems Children. The principles of child protection in the implementation of development of the main coaching against children who undergo criminal in a correctional institution children are: the principle of protection, the principle of non discrimination, the principle of the best interests for children, the principle of the right of life, grow and flourish, the principle of training and coaching, the principle of proportionate. In terms of nurturing a right to complain of the correctional institution for the protection of children (made of cement the principles of refuge in principle, against the best interests of the child, the principle of life grow and develop, the principle of development and coaching, the principle of proportional ) has done or accomplished.For the fulfillment of the rights of the child in his complaint made of cement a correctional institution and there are few obstacles to or derived from the correctional officers to undergo a criminal himself. Key words: complaint, children, protection of children Abstrak Artikel ilmiah ini membahas tentang Pemenuhan Hak Menyampaikan Keluhan Bagi Anak di Lembaga Pemasyarakatan Anak Blitar, dikaitkan dengan Prinsip Perlindungan Anak yang terdapat dalam Undang-Undang Nomor 11 Tahun 2012 tentang Sistem Peradilan Pidana Anak. Permasalahan yang diangkat oleh penulis, mengenai pelaksanaan pemenuhan hak menyampaikan keluhan bagi anak di Lembaga Pemasyarakatan Anak Blitar yang mencerminkan prinsip perlindungan anak. Kemudian dilanjutkan dengan mengetahui kendala dan upaya yang dilakukan oleh Lembaga Pemasyarakatan Anak Blitar dalam pemenuhan hak menyampaikan keluhan bagi anak di Lembaga Pemasyarakatan Anak Blitar. Jenis penelitian adalah penelitian empiris dengan metode pendekatan yuridis Â sosiologis. Dari hasil penelitian yang dilakukan maka dapat diketahui bahwa pelaksanaan hak menyampaikan keluhan bagi anak di Lembaga Pemasyarakatan Anak Blitar telah mencerminkan prinsip perlindungan anak yang terdapat dalam Undang-undang Nomor 11 Tahun 2012 tentang Sistem Peradilan Pidana Anak. Prinsip-Prinsip perlindungan anak dalam pelaksanaan pembinaan utamanya pembinaan terhadap anak yang menjalani pidana pada Lembaga Pemasyarakatan AnakÂ  diantaranya: prinsip perlindungan, prinsip non diskriminasi, prinsip kepentingan terbaik bagi anak, prinsip hak hidup, tumbuh dan berkembang, prinsip pembinaan dan pembimbingan, prinsip proporsional. Dalam pelaksanaan pembinaan utamanya pemenuhan hak menyampaikan keluhan bagi anak pada Lembaga Pemasyarakatan Anak Blitar keenam prinsip-prinsip perlindungan anak (prinsip perlindungan, prinsip non diskriminasi, prinsip kepentingan terbaik bagi anak, prinsip hak hidup, tumbuh dan berkembang, prinsip pembinaan dan pembimbingan, prinsip proporsional) telah dilaksanakan dan /atau terpenuhi. Pelaksanaan pemenuhan hak menyampaikan keluhan bagi anak pada Lembaga Pemasyarakatan Anak Blitar terdapat beberapa kendala dan upaya yang berasal petugas pemasyarakatan maupun dari anak yang menjalani pidana sendiri. Kata kunci: Keluhan, Anak, Perlindungan Anak